Prevalence and demographic risk factors of gastrointestinal symptoms in Tehran province (Italian Journal of Public Health, 2010)
Background: Gastrointestinal diseases are maladies that produce multiple symptoms. Suffering from thesesymptoms attributes people to an illness which they self-treat or seek medical care. The objective of thisstudy is to determine the prevalence of gastrointestinal (GI) symptoms and relation between somedemographic factors and GI symptoms in the Province of Tehran.Methods: This study was a cross-sectional household survey conducted from May 2006 to December 2007 inthe Province of Tehran, Iran. The questionnaire included personal and family characteristics such as age,gender, and educational level. In addition to this, interviewers asked about 10 GI symptoms.Results: A total of 30,334 subjects were included in the study, there were 15,165 men (50%). Among them,4,400 (14.5%) reported one or more GI symptom. Prevalence of GI symptoms included: heartburn 8.6%,bloating 7.6%, abdominal pain 6.2%, constipation 5.1%, anal pain 1.7%, weight loss 1.4%, diarrhea 1.1%,nausea and vomiting 1%, anal bleeding 0.8% and dysphagia 0.8%.Conclusions: The prevalence of GI symptoms in the population studied was lower than that reported in otherpopulations. Women had higher prevalence of GI symptoms. With the increase in educational level the chanceof have a GI symptom decreased. Singles reported symptoms less than married participants.
Keywords: gastrointestinal symptom; population-based study; Tehran